Innovative modeling: a diet-induced quail model for progressive pathological changes in uric acid metabolism disorders - Xu, Yi; Wang, Yu; Gao, Fujun; Lu, Chengjin; Liu, Shujia; Chen, Siying; Zhang, Xiaomeng; Lin, Zhijian; Zhang, Bing (Frontiers in Nutrition, 2025)
BackgroundDiseases associated with uric acid metabolism disorders, primarily hyperuricemia, uric acid nephropathy, and gouty arthritis, are increasingly prevalent worldwide. Recent research suggests that hyperuricemia, uric acid nephropathy, and gouty arthritis can be regarded as distinct phases of the same disease, characterized by elevated serum uric acid levels and the progressive pathological manifestations observed in clinical settings. Animal models play a crucial role in investigating disease mechanisms and therapeutic interventions. However, there are currently few animal models available that can accurately simulate human uric acid metabolism disorders on the same animal, particularly those exhibiting progressive pathological features.MethodsThis study established a quail model of urate metabolism disorder using 25-day-old male Defaike quails via dietary induction. The diet consisted of high-calcium/high-purine components, including 20% yeast extract and 30% bone extract powder, supplemented with 15 mL of 10% fructose water daily for 30 days. The model effectively recapitulated three progressive pathological stages: (1) Hyperuricemia; (2) Hyperuricemia with urate nephropathy; and (3) Hyperuricemia with gouty arthritis. In the simple hyperuricemia stage, serum uric acid levels significantly increased after 10 days of intervention, with no significant deposition of monosodium urate (MSU) crystals observed in the kidneys or synovial fluid. In the second stage, hyperuricemia combined with uric acid nephropathy, renal MSU crystals were deposited after 20 days, while serum uric acid levels remained elevated, and serum creatinine (CRE) and blood urea nitrogen (BUN) significantly increased, accompanied pathological changes in renal tissue. In the final stage, hyperuricemia combined with gouty arthritis, MSU crystals were deposited in joint synovial fluid after 30 days of intervention, and the inflammatory factor IL-1β levels were elevated in both serum and synovial fluid.ResultsOn day 10, the model quails exhibited significantly increased serum uric acid levels, indicating hyperuricemia. This condition was accompanied by a decreased uric acid excretion fraction and increased activities of liver uricase, xanthine oxidase (XOD), and adenosine deaminase (ADA). Additionally, there was a significant upregulation of GLUT9 mRNA levels in the kidney, accompanied by a downregulation of renal OAT1, OAT3, and ABCG2 mRNA levels. Although high serum uric acid levels have been observed at this time, no MSU crystals formation or acute inflammation-related manifestations have been noted. On day 20, urate crystals were observed in the kidneys of the model quails, accompanied by elevated serum CRE and BUN levels, alongside evident pathological damage indicative of uric acid nephropathy. Even if high serum uric acid levels persist on day 20, urate crystals and acute inflammation have not yet appeared in synovial fluid, further supporting the notion that crystal deposition is a gradual process rather than triggered by hyperuricemia. By day 30, urate crystals were detected in the synovial fluid of the model quails, and the levels of uric acid and inflammatory cytokine IL-1β in synovial fluid were significant increased, indicating the presence of gouty arthritis. This suggests that uric acid elevation precedes MSU crystal formation, and MSU deposition is a crucial event in the development of gouty arthritis. Furthermore, serum levels of inflammatory cytokines IL-6, TNF-α, and hs-CRP were elevated considerably throughout the modeling process.ConclusionThis diet-induced quail model successfully recapitulates the progressive pathological stages of human uric acid metabolism disorders, providing a valuable tool for investigating disease mechanisms and evaluating potential therapeutics.